The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s13256-023-03778-4
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral central retinal vein occlusion as an initial presentation of Waldenström macroglobulinemia: a case report

Abstract: Background Waldenström macroglobulinemia is a rare hematological malignancy and is the most common diagnosis in patients with hyperviscosity syndrome. Bilateral central retinal vein occlusion as an initial presentation of hyperviscosity syndrome in Waldenström macroglobulinemia is rare. Case presentation A 42-year-old Nepalese male presented with sudden-onset bilateral painless blurring of vision. Fundus examination revealed bilateral, diffusely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Subsequently, intravitreal bevacizumab injection was administered by a monocular trial in one eye, and serous macular detachment and visual acuity significantly improved 7 days after injection [13]. Shrestha et al [14] reported a case of macular edema due to WM treated with intravitreal bevacizumab and systemic therapy (bortezomib, DEX, and rituximab [VDR]). The patient received a total of six VDR regimens, and his vision significantly improved bilaterally to 6/9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, intravitreal bevacizumab injection was administered by a monocular trial in one eye, and serous macular detachment and visual acuity significantly improved 7 days after injection [13]. Shrestha et al [14] reported a case of macular edema due to WM treated with intravitreal bevacizumab and systemic therapy (bortezomib, DEX, and rituximab [VDR]). The patient received a total of six VDR regimens, and his vision significantly improved bilaterally to 6/9.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore macular edema develops into a chronic and refractory condition [15]. Cases reporting improvement in visual acuity after systemic treatment and intravitreal injection [13,14] also show that rapid treatment is advantageous for improving visual acuity, with a case that visited the hospital within 2 weeks of symptom onset [13] and a case that visited the hospital at 5 days after onset [14]. In our case, the delayed start of treatment for more than 1 year can be considered as the cause of the almost unresponsive macular edema even after intravitreal anti-VEGF injection or systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] HVS occurs in 10-30% of patients with WM, and WM accounts for nearly 85% of HVS cases. 9,10 In a cohort of 825 newly diagnosed WM patients, 14% developed symptoms consistent with HVS. 11 CXCR4 mutations, found in 30% of patients with WM, are associated with increased likelihood of developing HVS.…”
Section: Introductionmentioning
confidence: 99%